Aerosol emission and exposure in non-invasive ventilation - Petra Nikuri; Anthony Maalouf; Ahmed Geneid; Eero Pesonen; Enni Sanmark; Ville A. Vartiainen (Scientific Reports)
Abstract From the beginning of the COVID-19 pandemic, there has been concern among clinicians whether the use of high-flow nasal cannula (HFNC) and continuous positive airway pressure (CPAP) contributes to aerosol generation and consequently spreading of pathogens. Most guidelines still classify these treatments as high-risk aerosol-generating procedures. The aim of this study was to evaluate differences in aerosol emissions and exposure with CPAP and HFNC compared to no breathing aid (NBA). Aerosol emissions of 16 healthy volunteers using CPAP, HFNC and NBA were measured with a portable aerosol spectrometer. During each measurement, the volunteers were instructed consecutively to breathe normally, breathe deeply, cough and read aloud a predefined text. The Wilcoxon signed-rank test was used in statistical analysis. Non-invasive ventilation (CPAP, HFNC) does not produce significantly more aerosol than the same respiratory activities without a breathing aid (median CPAP-NBA − 4.54 1/L, p = 0.816, and HFNC-NBA 2.27 1/L, p = 0.244), deep breathing (median CPAP-NBA − 2.27 1/L, p = 0.378 and HFNC-NBA 4.55 1/L, p = 0.623), speaking (median CPAP-NBA 0 1/L, p = 0.0523 and HFNC-NBA 9.09 1/L, p = 0.0140), or coughing (median CPAP-NBA − 17.31 1/L, p = 0.587 and HFNC-NBA 1.92 1/L, p = 0.365). The results indicate that both CPAP and HFNC have no clinically meaningful impact on aerosol emission. Therefore, the use of CPAP or HFNC does not expose healthcare personnel to greater concentrations of aerosols when compared to normal breathing in healthy participants.